The interaction effects of risk factors for hypertension in adults: a cross-sectional survey in Guilin, China - Yu, Jian (BMC Cardiovasc Disord, 2016)
BACKGROUND: The prevalence of hypertension in adults is increasing each year and has become a main public health issue worldwide. We must consider the impact of both individual factors and interactions among these factors on hypertension in adults. This study was designed to elucidate the clinical and metabolic characteristics of the prevalence of hypertension in adults and to explore the risk factors and interactions among these factors in adults with hypertension. METHODS: We used overall random sampling to conduct a cross-sectional survey of 6660 individuals undergoing a health check from July to November 2012, the subjects were aged 20 to 89 years, including 3480 men and 3180 women. The survey content included a questionnaire, anthropometry, laboratory measurements, and liver Doppler ultrasonography. The clinical and metabolic characteristics were compared between the cases (adult hypertensive patients) and the controls (normotensives). The classification tree model and the non-conditional logistic regression were used to analyze the interactions of risk factors for hypertension in adults. RESULTS: In total, 1623 adult hypertensive patients (940 men and 683 women) were detected. The results showed that adult hypertensive patients were older and had higher levels of systolic blood pressure, diastolic blood pressure, body mass index, fasting plasma glucose, uric acid, triglycerides, total cholesterol, low-density lipoprotein cholesterol, and prevalence of non-alcoholic fatty liver disease (P < 0.001). The classification tree model comprising 5 layers, 39 nodes, and 20 terminal nodes showed that two variables, age and BMI, were closely related to hypertension in adults. The area under the receiver operating characteristic curve for classification tree model was 81.6 % (95 % CI: 80.6 % ~ 82.5 %). Both univariate and multivariate logistic regression analyses revealed that advanced age and high BMI had a significant positive interaction in terms of hypertension in adults. After controlling for confounding factors, the percentage of attributed interaction was 47.62 %. CONCLUSIONS: This study showed that age, BMI, UA, TG, and TC were closely associated with the risk of hypertension in adults, and the positive interaction effect between advanced age and high BMI was an important risk factor for the prevalence of hypertension in adults.